Comparative Analysis of Elementary School Student Knowledge Regarding Flood Mitigation in the Citarum Watershed - Sukono Sukono; Eman Lesmana; Herlina Napitupulu (Research Collaboration Community (RCC), 2020)
Flooding is a natural event, one of which is caused by the overflow of rivers. This disaster often occurs in the Dayeuhkolot area, Bandung Regency. Geographical conditions that are close to the flow of the Citarum River and the plains that are lower than the surrounding area cause this area to be flooded especially during the rainy season. This paper aims to analyze the effectiveness of disaster training given at a young age and analyze the effectiveness of training methods provided in the form of games and PowerPoint media. This activity is aimed at grade 6th students at BojongAsih Elementary School starting with the questionnaire I which functions as a pre-test and ends with questionnaire II which functions as a post-test. Questionnaires were given at the beginning and at the end to see the extent to which the material provided new influence and knowledge to BojongAsih Elementary School students. The results of the questionnaire showed that before counseling about flood mitigation, samples were categorized as having a good knowledge of 91% and having poor knowledge of 9%. After counseling about flood disaster mitigation using games and PowerPoint media there was an increase in knowledge, samples that had good knowledge were 98% and those with less good knowledge were 2%. Based on the pre-test and post-test results, this activity was proven successful in increasing the knowledge of BojongAsihElementary School related to flood mitigation.